Automation of ChIP-Seq Library Preparation for Next Generation Sequencing on the epMotion® 5075 TMX - Cheng Liu; Jesse Cassidy; Maryke Appel (BioTechniques)
ChIP-Seq library preparation can be a challenging procedure to automate because of its low ChIP DNA input. This Application Note describes the successful automation of Illumina ChIP-Seq library preparation on the Eppendorf epMotion 5075 TMX, using the KAPA High-Throughput Library Preparation Kit from Kapa Biosystems. Size-selected libraries were prepared from as little as 1 ng of fragmented ChIP DNA. To obtain the recommended 100 ng of library material for sequencing on the Illumina Genome AnalyzerIIx, only 18 amplification cycles were needed for 1 ng of input DNA, or 9 cycles when starting library construction with 10 ng of ChIP DNA.